2008
DOI: 10.2174/1874129000802010001
|View full text |Cite
|
Sign up to set email alerts
|

Status of the Emerging InAlN/GaN Power HEMT Technology

Abstract: Abstract:The InAlN/GaN heterojunction appears to be a new alternative to the common AlGaN/GaN configuration with higher sheet charge density and higher thermal stability, promising very high power and temperature performance as well as robustness. This new system opens up the possibility to scale the barrier down to 5 nm while maintaining nearly its ideal materials and device properties. The status, focussing on the lattice matched materials configuration, is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
47
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 28 publications
5
47
1
1
Order By: Relevance
“…In addition, a high thermal and chemical stability has been demonstrated for lattice-matched InAlN/ GaN HEMT, and devices operate up to 1000 C without showing serious performance degradation. 6 Motivated by these potential advantages mentioned above, significant progress with respect to device performance and structure has been achieved with this new InAlN/ GaN heterostructures during last five years. Alomari et al 5 reported a maximum drain current density of 2.4 A/mm in device with thermally generated oxide recess, while Wang et al 7 demonstrated a transconductance exceeding 800 mS/ mm in enhancement-mode device.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a high thermal and chemical stability has been demonstrated for lattice-matched InAlN/ GaN HEMT, and devices operate up to 1000 C without showing serious performance degradation. 6 Motivated by these potential advantages mentioned above, significant progress with respect to device performance and structure has been achieved with this new InAlN/ GaN heterostructures during last five years. Alomari et al 5 reported a maximum drain current density of 2.4 A/mm in device with thermally generated oxide recess, while Wang et al 7 demonstrated a transconductance exceeding 800 mS/ mm in enhancement-mode device.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The reason for the drive to InAlN is twofold. [1][2][3][4][5] The reason for the drive to InAlN is twofold.…”
mentioning
confidence: 99%
“…Moreover, great efforts have been made in the investigation of lattice-matched InAlN-barrier HEMTs since they could potentially present no strain, which could improve the heterostructure stability [10] and long term reliability. A higher 2-dimensional electron gas (2DEG) density would be induced mainly by the larger spontaneous polarization compared to the AlGaN barrier [10][11][12]. Jardel et al presented devices with excellent power performance even in Ku band [13], and Lee et al reported lattice-matched InAlN/GaN HEMTs with an InGaN back barrier on a SiC substrate showing a record f T of 300 GHz for 30 nm gate length devices [14].…”
Section: Introductionmentioning
confidence: 99%